Frontal fibrosing alopecia: possible association with leave‐on facial skin care products and sunscreens; a questionnaire study3. (30th June 2016) - Aldoori, N.; Dobson, K.; Holden, C.R.; McDonagh, A.J.; Harries, M.; Messenger, A.G.
Summary: Background: Since its first description in 1994, frontal fibrosing alopecia (FFA) has become increasingly common, suggesting that environmental factors are involved in the aetiology. Objectives: To identify possible causative environmental factors in FFA. Methods: A questionnaire enquiring about exposure to a wide range of lifestyle, social and medical factors was completed by 105 women with FFA and 100 age‐ and sex‐matched control subjects. A subcohort of women with FFA was patch tested to an extended British standard series of allergens. Results: The use of sunscreens was significantly greater in the FFA group compared with controls. Subjects with FFA also showed a trend towards more frequent use of facial moisturizers and foundations but, compared with controls, the difference in frequencies just failed to reach statistical significance. The frequency of hair shampooing, oral contraceptive use, hair colouring and facial hair removal were significantly lower in the FFA group than in controls. Thyroid disease was more common in subjects with FFA than controls and there was a high frequency of positive patch tests in women with FFA, mainly to fragrances. Conclusions: Our findings suggest an association between FFA and the use of facial skin care products. The high frequency of sunscreen use in patients with FFA, and the fact that many facial skin care products now contain sunscreens, raises the possibility of a causative role for sunscreen chemicals. The high frequency of positive patch tests in women with FFA and the association with thyroid disease may indicate a predisposition to immune‐mediated disease. Abstract : What's already known about this topic? Frontal fibrosing alopecia (FFA) is an inflammatory scarring alopecia that mainly involves the frontal and frontal/temporal hairline and eyebrows. The histopathology is identical to that of lichen planopilaris. FFA mainly affects postmenopausal women although it also occurs in younger women and occasionally in men. First reported in 1994, FFA remained rare during the 1990s but has become increasingly common in the last 10–15 years. What does this study add? Leave‐on facial skin care products are implicated in the aetiology of FFA. It is suggested that sunscreen chemicals play a causative role. It is suggested that there is an increased predisposition to immune‐mediated disease in FFA. Linked Comment: Donati. Br J Dermatol 2016;175 :675–676 . Plain language summary available online